Pigments and glassy matrix of the 17th-18th century enamelled French watches: A non-invasive on-site Raman and pXRF study - Colomban, Philippe; Kirmizi, Burcu; Gougeon, Catherine; Gironda, Michele; Cardinal, Catherine (ELSEVIER FRANCE-EDITIONS SCIENTIFIQUES MEDICALES ELSEVIER, 2020)
Twelve rare watches with painted enamels, mostly produced in France, from the 17th and 18th centuries in the collections of Musee du Louvre in Paris were analysed on-site in order to characterize the materials used in their enamels and the enamelling technique. All the watches were analysed by mobile Raman microspectroscopy and five of them were also analysed by pXRF. Pigments (Naples Yellow pyrochlore, hematite, carbon, lapis lazuli, arsenic sulphide, manganese oxides), opacifiers (cassiterite, lead arsenates) and corresponding lead-rich glassy silicate matrices were identified by one or two methods. Similar to the oil painting or tempera techniques, different hues of the related enamels were obtained by mixing many colouring agents, rather than using 'pure' enamels as in the case of Limoges enamelled objects. Lead arsenate apatite detected in some of the 17th century blue enamels is related to the use of European arsenic-rich cobalt ores, as also characterized in the blue (soft-paste) porcelain decors and high-quality Limoges enamels. The presence of colloidal gold (Au nanoparticles) was indirectly detected by the Raman technique in the 18th century watches and confirmed by pXRF. At least three types of Naples Yellow pigment were identified with Sb-rich, Sn-rich and mixed Sb-Sn-Fe-Zn compositions. (C) 2020 Elsevier Masson SAS. All rights reserved.
Keywords: Enamels; Pigments; Cobalt; Arsenic; Naples yellow; 17th century; EUROPEAN COBALT SOURCES; PYROCHLORE FAMILIES; GENUINE ARTIFACTS; YELLOW PIGMENTS; LIMOGES ENAMELS; PAINTED ENAMELS; POTTERY GLAZES; NAPLES-YELLOW; FORCE-FIELD; IDENTIFICATION; Archaeology; Art; Chemistry; Geology; Materials Science; Spectroscopy